The potential of telemedicine in alleviating out-of-pocket costs for oncological patients in the Brazilian public healthcare system - Favoreto-Neto, José; Aguiar, Pedro, Junior; Klerton-Luz-Araujo, José; del-Giglio, Auro (Brazilian Journal of Oncology, 2023)
Despite the absence of data regarding direct costs for healthcare, oncological patients from the Brazilian Unified Public Healthcare System often face significant financial burden due to out-of-pocket costs associated with their treatment. These costs include expenses for transportation, meals, non-covered medications, and the time spent on medical visits, tests, and treatments. This paper used data previously collected from two studies conducted with oncological patients in different regions of Brazil. These studies evaluated out-of-pocket costs incurred by the patients when receiving care through the Brazilian Unified Public Healthcare System. We estimated that by removing transportation-related costs, OPC would be reduced by 62% (95%CI: 57%-67%) in the southeast region and 60% (95%CI: 56%-64%) in the northeast region. This reduction was statistically significant in both regions (p<0.0001). We conclude that substituting regular face-to-face visits with telemedicine, whenever possible, can significantly decrease OPC for patients and potentially contribute to higher treatment adherence among underserved populations.
Keywords: Telemedicine; Cancer care facilities; Health expenditures; Unified health system; Economics; Pharmaceutical